Peran Total Quality Management Terhadap Cacat Produk (Studi Kasus pada klaster IKM Fabrikasi Logam di Kabupaten Bogor) - Nurdiansah , Angga; Cahyadi , Eko Ruddy; Slamet , Alim Setiawan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
Small and medium entreprises (SMEs) are the largest contributors to state revenue in Indonesia, but in factthe product quality of metal fabrication SMEs has a negative trend. This is because the products of metal fabricated SMEs have a significant level of defects. the purpose of this study such as ; (1) to analyze the level of defect, (2) to analyze the application of Total Quality Management (TQM) (3) to analyze the factors which significanly reduce the defect. The metal fabrication SMEs cluster located in Gunungsari, Pasirmukti and Tarikolot, the three villages are located in Citeureup sub-district, Bogor regency. This study used 109 respondent and processed multiple linear regression. TQM has significantly impact to reduce product defect.This SMEs needs to consistently apply TQM, so that product defects can be reduced